Can Serum Thyroglobulin Levels Help to Identify the Involved Neck Compartment of Differentiated Thyroid Carcinoma? - Bahçecioğlu, Adile Begüm; Ozkan, Elgin; Araz, Mine; Elhan, Atilla Halil; Erdoğan, Murat Faik (Hormone and Metabolic Research, 2022)
We aimed to evaluate the predictive ability of serum thyroglobulin (Tg) levels on the localization of the metastatic lymph node compartments in locoregional metastases of papillary thyroid cancer (PTC). This retrospective study included 143 patients who underwent neck dissections for a total of 172 for persistent/recurrent locoregional PTC. They were grouped according to the localization of lymph node metastasis (LNM): Central (C-LNM), Lateral (L-LNM), both central and lateral LNM (C+L LNM). To confirm that the Tg cutoff discriminated LNM localizations, the sample was categorized as suppressed (<0.1 mU/l) or non-suppressed (>0.1 mU/l) according to TSH and ROC analysis. Mixed-effects models were used to investigate the effect of LNM localization on Tg levels and to eliminate the confounding effects of TSH, tumor burden (defined as the number and the largest diameter of LNM), and RAI. Mean Tg levels were 1.43 μg/l for C-LNM (n=47), 3.7 μg/l for L-LNM (n=99), and 8.60 μg/l for C+L LNM (n=26). Independent of TSH, tumor burden and RAI, the mean Tg levels of L-LNM and C+L LNM groups were not significantly different, while that of C-LNM was significantly lower than those of L-LNM and C+L LNM. To discriminate C-LNM from L-LNM and C+L LNM in patients with TSH>0.1 mU/l, the optimal cutoff for Tg was 1.05 μg/l (sensitivity=74.7%, specificity=70.4%, PPV=87.7%). L-LNM increases serum Tg levels more than C-LNM in persistent/recurrent locoregional nodal disease of PTC. Tg above 1.05 μg/l may indicate lateral LNM. Tg may be an important marker for the localization of LNM in the neck.
Keywords: papillary thyroid carcinoma; thyroglobulin; locoregional metastasis; cervical lymph node compartment